The history of the birth of the secular Islamic state of Turkey and the idea of the renewal of Mustafa Kemal Ataturk - Hannanong, Ismail; Murniati, Murniati; Hasaruddin, Hasaruddin; Syukur, Syamzan (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This article discusses the history of the birth of the secular Islamic State of Turkey and the ideas of reform carried out by Mustafa Kemal Ataturk in various fields and its transformation into a modern, secular state. The method used in this research is a literature review using a qualitative approach. The analysis used to analyze the data is content analysis. The research results show that Mustafa Kemal Ataturk was one of the qualified Islamic reformers of the 19th century. He has made a major contribution to changing the mindset of Turkish society. By changing the old order that had become a tradition in the Ottoman Empire, and forming it into a new face with a style of thinking that actually did not change